Measuring the performance of banks: Theory, practice, evidence, and some policy implications - Joseph P. Hughes; Loretta J. Mester (Rutgers University, Department of Economics, 2013)
The unique capital structure of commercial banking - funding production with demandable debt that participates in the economys payments system - affects various aspects of banking. It shapes banks comparative advantage in providing financial products and services to informationally opaque customers, their ability to diversify credit and liquidity risk, and how they are regulated, including the need to obtain a charter to operate and explicit and implicit federal guarantees of bank liabilities to reduce the probability of bank runs. These aspects of banking affect a banks choice of risk vs. expected return, which, in turn, affects bank performance. Banks have an incentive to reduce risk to protect the valuable charter from episodes of financial distress and they also have an incentive to increase risk to exploit the cost-of-funds subsidy of mispriced deposit insurance. These are contrasting incentives tied to bank size. Measuring the performance of banks and its relationship to size requires untangling cost and profit from decisions about risk versus expected-return because both cost and profit are functions of endogenous risk-taking. This chapter gives an overview of two general empirical approaches to measuring bank performance and discusses some of the applications of these approaches found in the literature. One application explains how better diversification available at a larger scale of operations generates scale economies that are obscured by higher levels of risk-taking. Studies of banking cost that ignore endogenous risk-taking find little evidence of scale economies at the largest banks while those that control for this risk-taking find large scale economies at the largest banks - evidence with important implications for regulation.
Keywords: G1; 330; bank; efficiency; risk; cost; profit; scale economies; X-inefficiency